Chronic Osteomyelitis with Staphylococcus aureus Deformation in Submicron Canaliculi of Osteocytes: A Case Report - de Mesy Bentley, Karen L. (JBJS Case Connect, 2018)
CASE: A patient presenting with an infected diabetic foot ulcer and Staphylococcus aureus chronic osteomyelitis was studied to validate the clinical importance of bacterial colonization of osteocytic-canalicular networks, as we recently reported in a mouse model. We utilized transmission electron microscopy to describe the deformation of S. aureus, from round cocci to rod-shaped bacteria, in the submicron osteocytic-canalicular networks of amputated bone tissue. CONCLUSION: To our knowledge, this is the first evidence of S. aureus deformation and invasion of the osteocytic-canalicular system in human bone, which supports a new mechanism of persistence in the pathogenesis of chronic osteomyelitis.